Bound states of the hydrogen atom in high‐density plasmas. Issue 10 (5th April 2022) - Shalenov, Erik O.; Nuraly, Askhat T.; Dzhumagulova, Karlygash N.
Abstract: In this work, the interaction potential of dense plasma particles, which takes into account the effect of quantum non‐locality as well as electronic correlations, was used to solve the Schrödinger equation for the hydrogen atom. Energies of bound states were calculated. The results obtained are in good agreement with the results of other authors.